2009
DOI: 10.1158/1535-7163.mct-08-0812
|View full text |Cite
|
Sign up to set email alerts
|

Local enzymatic hydrolysis of an endogenously generated metabolite can enhance CPT-11 anticancer efficacy

Abstract: Irinotecan (CPT-11) is a clinically important anticancer prodrug that requires enzymatic hydrolysis by carboxyesterase to generate the active metabolite SN-38. However, SN-38 is further metabolized to inactive SN-38 glucuronide (SN-38G), thus diminishing the levels of active SN-38. Although exogenously administered glucuronide drugs are being investigated for cancer therapy, it is unknown if endogenously generated camptothecin glucuronide metabolites can be used for tumor therapy. Here, we tested the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, the FDA's recommendation has been questioned because Gilbert's patients receiving CPT-11 therapy have been shown to experience toxicity to a lesser degree than previously anticipated (16,17). After its excretion into the bile, SN-38G reaches the gastrointestinal tract, where it is subjected to bacterial β-glucuronidase β-linkage cleavage that produces a free SN-38 aglycone (18)(19)(20)(21). Recent findings, using specific bacterial β-glucuronidase inhibitors to protect mice from CPT-11-induced late diarrhea, strongly suggest that the enterohepatic circulation of SN-38 plays an essential role in the delayed diarrhea (18,22).…”
Section: δHepmentioning
confidence: 99%
“…However, the FDA's recommendation has been questioned because Gilbert's patients receiving CPT-11 therapy have been shown to experience toxicity to a lesser degree than previously anticipated (16,17). After its excretion into the bile, SN-38G reaches the gastrointestinal tract, where it is subjected to bacterial β-glucuronidase β-linkage cleavage that produces a free SN-38 aglycone (18)(19)(20)(21). Recent findings, using specific bacterial β-glucuronidase inhibitors to protect mice from CPT-11-induced late diarrhea, strongly suggest that the enterohepatic circulation of SN-38 plays an essential role in the delayed diarrhea (18,22).…”
Section: δHepmentioning
confidence: 99%
“…23 In a recent study, we demonstrated that stable expression of a membrane-tethered form of bG on EJ bladder cancer cells increased their sensitivity to SN-38G and enhanced the therapeutic efficacy of CPT-11 in vivo. 24 We transduced the tumor cells ex vivo with a retroviral vector to achieve bG expression. Because this approach is difficult to use clinically, in the present study we used an adenoviral (Ad) vector for gene transfer into tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that mammalian GUS may convert SN-38G back to SN-38 within the tumor and thus increase the concentration of active drug (SN-38) in the tumor. [18][19][20] Therefore, any inhibitor of bacterial GUS used therapeutically should not inhibit the mammalian GUS because this may decrease the efficacy of irinotecan at the site of the tumor. Therefore, we tested the three most potent drugs from the screen-nialamide, isocarboxazid, and amoxapinein enzyme assays identical to the E. coli GUS enzyme assay, except for the use of mammalian GUS purified from B. taurus liver.…”
mentioning
confidence: 99%